2020
DOI: 10.15804/tner.20.61.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Employability of National Youth Service Corps Members for Sustainable Development in South-East, Nigeria

Abstract: Th is paper examines the innovation and employability of National Youth Service Corps (NYSC) members for sustainable development in south-east Nigeria. Th e research design employed for this study was a descriptive survey. Th e population for this study comprises all NYSC members serving in southeast Nigeria. A purposive sampling technique was used to sample all 2019 Batch "C" who participated in the Post Mobilisation Workshop held on 27t -29t January 2020. Also, a simple random sampling technique was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…The current research confirmed that innovation capability has a significant play in college students’ employability, which echoes the findings of the scarce previous studies ( Okafor et al, 2020 ; Rees, 2021 ). The world is entering into an era of knowledge economy that prioritizes intellectual property, creativity, and competitive advantage.…”
Section: Discussionsupporting
confidence: 90%
“…The current research confirmed that innovation capability has a significant play in college students’ employability, which echoes the findings of the scarce previous studies ( Okafor et al, 2020 ; Rees, 2021 ). The world is entering into an era of knowledge economy that prioritizes intellectual property, creativity, and competitive advantage.…”
Section: Discussionsupporting
confidence: 90%